(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study examines the names of officials in Russian and Uzbek languages, focusing on their linguistic characteristics, cultural significance, and usage in official contexts. Through a comparative analysis of naming conventions and linguistic features, the research sheds light on the similarities and differences between the two languages in terms of official titles and designations. Additionally, the study explores the historical and sociocultural factors that influence the formation and evolution of official names in Russian and Uzbek languages, highlighting the importance of linguistic diversity and cultural heritage in administrative discourse.